2020
DOI: 10.1111/pin.12954
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of clear cell carcinoma of the ovary: A basic view based on cultured cells and modern view from comprehensive approaches

Abstract: Clear cell carcinoma (CCC) is a distinct histologic type of ovarian carcinoma. CCC is more frequent in Japan than in the Western world. CCC is chemo‐resistant and often associated with paraneoplastic thromboembolism. Histologically, CCC is characterized by both cancer cells and stromas, being concordant with the cytological features. Clear cells contain abundant glycogen. Hepatocyte nuclear factor‐1β is a specific marker of CCC, and is likely to be involved in glucose metabolism. Extracellular matrix (ECM)‐dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Therefore, biomarkers related to iron death may be potential diagnostic biomarkers and therapeutic targets for patients with renal cancer [13]. As a common subtype of renal cell carcinoma, in recent years, many medical researchers have devoted themselves to studying the occurrence, development, and treatment of renal clear cell carcinoma [14][15][16][17][18]. Many studies have shown that different subtypes of renal cell carcinoma have different clinical characteristics and results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biomarkers related to iron death may be potential diagnostic biomarkers and therapeutic targets for patients with renal cancer [13]. As a common subtype of renal cell carcinoma, in recent years, many medical researchers have devoted themselves to studying the occurrence, development, and treatment of renal clear cell carcinoma [14][15][16][17][18]. Many studies have shown that different subtypes of renal cell carcinoma have different clinical characteristics and results.…”
Section: Discussionmentioning
confidence: 99%
“…These "clear cell" malignancies include cancers of the kidney, ovary, breast, endometrium, and colorectum (23)(24)(25)(26). The two most common clear cell cancersrenal and ovarian-have been well-characterized molecularly and histologically and provide useful systems to interrogate the roles of glycogen in tumorigenesis (26)(27)(28).…”
Section: Common Mediators Of Tumor Glycogenesismentioning
confidence: 99%
“…Additional research is also required to minimize adverse events that can occur when targeting metabolic processes which are important in both normal and malignant cells. This is highlighted by toxicities that have been reported from trials of 2DG against a range of advanced solid tumors, where the clinically tolerable dose of this agent was accompanied by significant adverse events including cardiac and gastrointestinal toxicities and neutropenia (28,29), with one patient experiencing a fatal cardiac arrest (96,102).…”
Section: Pharmacological Disruption Of Glycogen Metabolism In Cancermentioning
confidence: 99%
“…The most significant terms in Li signature were associated with meiosis, mismatch repair, and (unexpectedly) with glycogen biosynthesis ( Figure 4 ). Interestingly, there were previously only indirect links reported for the glycogen metabolism and Lynch syndrome ( Kato, 2020 ) or MSI ( Krausova and Korinek, 2014 ; Oh et al, 2016 ), e.g., through the Wnt signaling pathway ( Krausova and Korinek, 2014 ). In Danaher signature, the most significant terms were associated with mismatch repair and with somatic hypermutation of immunoglobulin genes and physiologically related processes: somatic diversification of immune receptors and immunoglobulins ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%